THE ECONOMIC IMPACT OF THE ACTIVITIES OF LOW-COST CARRIERS ON THE DEVELOPMENT OF THE AVIATION INDUSTRY - VYSOTSKA, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the performance of low-cost air carriers in the regional context and in comparison with the activities of classical airlines. The tendency of growth of performance indicators of airline companies that have used this model during all the years since its inception is determined.The main factors influencing the growth of the low-cost segment in the total volume of air transportation are analyzed. It is determined that the dynamic growth to 31% of the total number of air transportation in the world is due to an increase in the number of passengers as a result of efficiency measures taken by low-cost airlines aimed at increasing the passenger load factor, reducing costs and improving the organizational structure.The tendency of development of low-cost airlines in the Ukrainian aviation market is characterized.A comparison of the LCC and FSC models by the main features is made. The cost structure, the difference in costs of airlines using different models, and the reasons for this are described. The route models used by classic airlines and low-cost airlines are described. The impact of primary and secondary costs from the introduction of a new low-cost airline on the costs of other economic agents is described. The effects arising from the introduction of a new low-cost airline are determined.The consequences of changes in the LCC and FSC models caused by the convergence process are investigated. The signs of a hybrid model that can become more attractive to a wide range of consumers, which, in turn, will contribute to the growth of passenger traffic and strengthen the airline's position in the market, are determined.
Keywords: LCC (Low-cost carrier); FSC-Full Service carrier; convergence of models; airline costs; airline effects